Sebaran Data Pasien Rawat Inap Covid-19 Dengan Komplikasi Penyakit Neurologis Diruang Isolasi Kemuning Dalam Periode Juli 2020-Juli 2021 Di RSU Darmayu Ponorogo - Riga Abida Rosyid; Mutia Sinta (JURNAL ILMIAH NUSANTARA, 2025)
Several studies have reported evidence that SARSCoV-2 not only attacks the respiratory system but can also attack other organs including the neurological system. Initial data from the Darmayu Ponorogo General Hospital in the Kemuning Isolation Room for the period July 2020 to July 2021 found Covid-19 patients with complications of neurological diseases such as infarct stroke, bleeding stroke, vertigo and epilepsy. Therefore, based on the description above, the author is interested in conducting research on the distribution of data on Covid-19 inpatients with complications of neurological disease in the yellow isolation room in the period July 2020-July 2021 at Darmayu Ponorogo General Hospital. This study uses an observational description of the design using secondary data. This study only wanted to see the distribution of data on Covid-19 inpatients with complications of neurological diseases. The population and sample in this study were all Covid-19 inpatients with complications of neurological disease in the Kemuning Isolation Room in the period July 2020-July 2021 at Darmayu Ponorogo General Hospital as many as 53 respondents. The data analysis method used in this study is univariate analysis, this is done with the aim of seeing a picture of the frequency distribution of Tables and Graphs regarding the distribution of data on Covid-19 inpatients with complications of neurological disease in the Kemuning Isolation Room in the period July 2020-July 2021 in RSU Darmayu Ponorogo. And from the results of the analysis, it can be seen that most of the Covid-19 inpatients in the Isolation Room of Darmayu Ponorogo General Hospital experienced complications of neurological disease in the form of infarction stroke, namely as many as 27 (50.9%) people, as many as 15 (28.3%) people experiencing complications. neurological disease in the form of bleeding stroke, as many as 10 (18.9%) people experienced complications of neurological disease in the form of vertigo and as many as 1 (1.9%) people experienced complications of neurological disease in the form of epilepsy